2008
DOI: 10.1097/01.pcc.0000298654.92048.bd
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life practices in seven Brazilian pediatric intensive care units

Abstract: The incidence of life support limitation has increased among Brazilian PICUs but with significant regional differences. Do-not-resuscitate orders are still the most common practice, with scarce initiatives for withdrawing or withholding life support measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 38 publications
3
51
1
9
Order By: Relevance
“…9 Lago ve arkadaşları-nın ÇYB ünitesinde yapmış olduğu çalışmada mortalite oranını %6,9 olduğunu belirtmişlerdir. 20 Çalışmamızdaki mortalite oranlarımızın literatür ile benzer düzeyde olduğunu gördük.…”
Section: Discussionunclassified
“…9 Lago ve arkadaşları-nın ÇYB ünitesinde yapmış olduğu çalışmada mortalite oranını %6,9 olduğunu belirtmişlerdir. 20 Çalışmamızdaki mortalite oranlarımızın literatür ile benzer düzeyde olduğunu gördük.…”
Section: Discussionunclassified
“…6 Several studies have been performed investigating ELDs in children in a variety of settings and causes of death. 3,4,[7][8][9][10][11][12][13][14][15][16] Many of these studies examined in particular ELDs in neonatal care or ELDs in pediatric intensive care units. 8,[11][12][13][14][15][16] Among the studies that focussed on different pediatric settings, a Dutch study performed in 2005 showed an ELD rate of 36% in all dying children suffering from a variety of diseases with an age range from 1 to 17 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Antecedents of the Theoretical Phase Antecedents Authors Establishment of an irreversible or incurable disease/irrecoverable situation/ irreversibility of the clinical condition. 5,12,18-38 Kipper et al, 2005;Casanueva Mateos et al, 2005;Salas Arrambide et al, 2005;Vernon et al, 1993;Anderson et al, 1994;Levetown et al, 1994;Carvalho et al, 2001;Meyer et al, 2002;Torreão et al, 2004;Lago et al, 2005;Rotta, 2005;Sharman et al, 2005;Tonelli et al, 2005;Robinson et al, 2006;Lago et al, 2007;Longden, Mayer, 2007;Martino Alba et al, 2007;Inwald, 2008;Tagarro García et al, 2008 Clear and effective communication between medical team, child, and family. 5,12,18,19,25,26,33-35,39-44 Kipper et al, 2005;Casanueva Mateos et al, 2005;Salas Arrambide et al, 20...…”
mentioning
confidence: 96%